Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s42003-021-02319-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint control of visually guided actions involves concordant increases in behavioural and neural coupling

Abstract: It is often necessary for individuals to coordinate their actions with others. In the real world, joint actions rely on the direct observation of co-actors and rhythmic cues. But how are joint actions coordinated when such cues are unavailable? To address this question, we recorded brain activity while pairs of participants guided a cursor to a target either individually (solo control) or together with a partner (joint control) from whom they were physically and visibly separated. Behavioural patterns revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…A growing body of literature shows neuronal synchronization that appeared across brains during meaningful social interaction ( Oldham et al 2018 ; Valencia and Froese 2020 ). Recent findings extend knowledge about human cognition and interpersonal interaction by showing an increase of both neuronal activities ( Painter et al 2021 ) and acquisition of new knowledge ( Danilov et al 2019 ; Danilov and Mihailova 2021a , 2021b ) in subjects in the absence of sensory cues between them (any verbal and non-verbal communication) in all the above experiments. These outcomes highlight the contribution of interpersonal interaction to cognition from the onset, discussed already by Vygotsky ( 2016 ).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…A growing body of literature shows neuronal synchronization that appeared across brains during meaningful social interaction ( Oldham et al 2018 ; Valencia and Froese 2020 ). Recent findings extend knowledge about human cognition and interpersonal interaction by showing an increase of both neuronal activities ( Painter et al 2021 ) and acquisition of new knowledge ( Danilov et al 2019 ; Danilov and Mihailova 2021a , 2021b ) in subjects in the absence of sensory cues between them (any verbal and non-verbal communication) in all the above experiments. These outcomes highlight the contribution of interpersonal interaction to cognition from the onset, discussed already by Vygotsky ( 2016 ).…”
Section: Introductionsupporting
confidence: 74%
“…Empirical evidence shows that emotion sharing happens without sensory cues and even awareness of the existence of emotional stimuli ( Tamietto et al 2009 ). Social interaction without sensory cues has been recently registered and presented in the neuroscience literature, showing coordinated neuronal activities in subjects in the absence of sensory cues between them (e.g., Painter et al 2021 ; Fishburn et al 2018 ; Valencia and Froese 2020 ). Recent studies also show an increase in acquiring new knowledge in the same conditions for subjects ( Danilov et al 2019 ; Danilov and Mihailova 2020 , 2021a , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis revealed evidence of statistically significant inter-brain synchrony while people were cooperating, with large overall effect sizes in both frontal and temporoparietal areas [14]. Apart from these reviews [9,14], another neuroscience study by Painter et al [15] registered neuronal coordination in the inter-brain experiment during coordinated mental activity without sensory cues, placing subjects in different isolated locations. Even though these two reviews [9,14] revealed significant inter-brain synchrony while people were cooperating, the data do not guide a conclusion about increased cooperative neuronal activity only due to interaction without sensory cues.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these two reviews [9,14] revealed significant inter-brain synchrony while people were cooperating, the data do not guide a conclusion about increased cooperative neuronal activity only due to interaction without sensory cues. From mentioned above research, only limited studies [10][11][12][13]15] accounted for certain features of the mother-newborn model in their research designs: solving the shared cognitive problem without communication in the dyads. Other studies did not concern studying inter-brain activity in pairs without sensory cues aiming at another research problem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literary insights showed coordinated neuronal activity in subjects during meaningful social interactions [34,35]. However, increased neuronal activities [36,37] and improvement in learning skills were observed [33,[38][39][40][41][42] in the absence of sensory cues (without communication) between the subjects. Another study [43] showed 32% increased performance in 13 dyad experiments conducted on 58 mothers and 68 children, aged 8-10 years, who were asked to solve unintelligible tasks without sensory clues, although familiar to the mothers.…”
Section: Introductionmentioning
confidence: 99%